STRATEGI PENGEMBANGAN USAHA SAPI POTONG (STUDI KASUS CV MITRA TANI FARM) - Shally Alpriany Aisyah; Bunasor Sanim; Agus Maulana (School of Business, Bogor Agricultural University (SB-IPB), 2013)
ABSTRACTThe purpose of this study were to 1) analyze the internal and external environmental conditions of CV Mitra Tani Farm, 2) identify and define strategies that affect the cattle breeding business development at CV Mitra Tani Farm, and 3) set the strategic priorities in the development of cattle breeding business in CV Mitra Tani Farm. Analysis strategies model (David, 2009) used were the analysis of the internal and external environment, strategy formulation and strategic priorities. At the stage of strategy formulation, SWOT 4 Quadrants were used. The results showed that the difference between the weighted scores of opportunities and threats as well as strengths and weaknesses is located in first quadrant of the SWOT 4 quadrant matrix. The first quadrant (growth quadrant) has eight strategies, but only three can be applied appropriately. The results of the value of interest using quantitative strategic planning matrix strategy used is the market expansion strategy, then the strategy of product development, and concentric diversification strategy. Therefore, in carrying out market expansion strategy, CV Mitra Tani Farm needs to do breakthrough campaign. In product development strategy, preferably CV Mitra Tani Farm makes processed beef products which are unique and still rare in the market today.Keywords: strategy, business beef cattle, CV Mitra Tani Farm, SWOT 4K, QSPMABSTRAKTujuan penelitian ini yaitu 1) menganalisis kondisi lingkungan internal dan eksternal CV Mitra Tani Farm, 2) mengidentifikasi dan menetapkan strategi yang memengaruhi dalam pengembangan bisnis sapi potong di CV Mitra Tani Farm, dan 3) menetapkan prioritas strategi dalam pengembangan usaha peternakan sapi potong di CV Mitra Tani Farm. Model analisis strategi (David, 2009) yang digunakan yaitu analisis lingkungan internal dan eksternal, perumusan strategi dan prioritas strategi. Pada tahap perumusan strategi digunakan SWOT 4 Kuadran. Hasil penelitian menunjukkan bahwa selisih skor terbobot antara peluang dan ancaman serta kekuatan dan kelemahan, diketahui CV Mitra Tani Farm berada pada kuadran satu matriks SWOT 4 Kuadran. Kuadran pertama (kuadran pertumbuhan) memiliki delapan strategi, namun hanya tiga yang dapat diterapkan secara tepat. Hasil nilai ketertarikan menggunakan quantitatif strategic planning matrix strategi yang digunakan yaitu strategi perluasan pasar, kemudian strategi pengembangan produk, strategi diversifikasi konsentrik. Oleh karena itu, dalam menjalankan strategi perluasan pasar, CV Mitra Tani Farm perlu melakukan trobosan promosi. Dalam strategi pengembangan produk, sebaiknya CV Mitra Tani Farm membuat produk olahan daging sapi yang unik dan masih jarang di pasar saat ini. Kata kunci: strategi, usaha sapi potong, CV Mitra Tani Farm, SWOT 4K, QSPM